Role of ketogenic and low-carbohydrate diets in the pathogenesis and treatment of obesity and diabetes mellitus type 1 and 2 - A Literature Review - Bąk, Dominika; Buszek, Julia; Czerniak, Piotr; Antoszewska, Adrianna; Bargiel, Weronika; Wajdowicz, Halszka; Warzocha, Mateusz; Sokołowska, Aldona (Journal of Education, Health and Sport, 2025)
Introduction: Ketogenic and low-carbohydrate diets are characterized by a significant reduction in daily carbohydrate intake, resulting in ketone bodies becoming an alternative energy source to glucose. Studies over the past decade have confirmed the therapeutic potential of the ketogenic diet in such disease entities as diabetes, polycystic ovary syndrome, acne, cancer, neurological diseases. In recent years, there has been a marked increase in patients with obesity and diabetes mellitus type 2, which has increased the number of studies on the impact of a carbohydrate-restricted diet on the pathogenesis and therapeutic process in this disease. This paper comprehensively analyzes the pathogenesis of obesity, diabetes mellitus type 1 and 2, and the effect of carbohydrate-restricted diet on these disease. Aim of the Study: The purpose of this study is to examine the effects of low-carbohydrate and ketogenic diets on the pathogenesis and treatment of obesity, type 1 and 2 diabetes mellitus. Materials and Methods: An analysis of papers available in PubMed was performed. The following keywords were used : non-carbohydrate diet, ketogenic diet, obesity, diabeletes mellutis type 1, diabetes mellutis type 2 Basic results: The ketogenic diet has a proven effective effect in reducing body weight, and thus shows a preventive effect on the development of type 2 diabetes. Low-carbohydrate diets improve glucose control and lower HbA1c levels. In addition, such a dietary pattern can help reduce the dose of hypoglycemic medications. Conclusion: According to the recommendations, there is no single optimal nutritional model in patients with diabetes, while the use of low-carbohydrate and ketogenic diets can lead to the desired results and achieve therapeutic goals in patients with diabetes.